2018
DOI: 10.31436/imjm.v17i2.996
|View full text |Cite
|
Sign up to set email alerts
|

Transformational and Transactional Leadership Styles in Enhancing Nurse Educator’s Job Satisfaction: An Integrative Analysis of Conventional and Islamic Approaches

Abstract: As nursing education gets more complex, leadership styles employed in these nursing training institutions played a crucial role in achieving nurse educators’ job satisfaction. As such, this study intends to elicit attributes and practices of nursing academic leaders’ transformational and transactional leadership styles in enhancing the job satisfaction of nurse educators. The qualitative method used for the study was based on the phenomenological approach to gather an in-depth understanding of human behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Transformational leaders have demonstrated their ability to improve subordinates' job satisfaction and performance in the context of Indonesia's Islamic education sector despite being badly hit by the COVID-19 pandemic (Noor Azizah et al, 2020). This is corroborated by Moey and Hashi (2018) who studied nine nurse educators and found that leaders at Malaysian nursing schools play critical roles in elevating the nurse educators' job satisfaction. This is because nurse educators who practice transformational leadership always inspire their team members to strive for greater success than the intended outcomes.…”
Section: Discussionmentioning
confidence: 68%
“…Transformational leaders have demonstrated their ability to improve subordinates' job satisfaction and performance in the context of Indonesia's Islamic education sector despite being badly hit by the COVID-19 pandemic (Noor Azizah et al, 2020). This is corroborated by Moey and Hashi (2018) who studied nine nurse educators and found that leaders at Malaysian nursing schools play critical roles in elevating the nurse educators' job satisfaction. This is because nurse educators who practice transformational leadership always inspire their team members to strive for greater success than the intended outcomes.…”
Section: Discussionmentioning
confidence: 68%